COMPREHENSIVE STUDY ON COPPER SLAG UTILIZATION: APPLICATIONS, CHEMICAL PROPERTIES, AND FUTURE DIRECTIONS - Zanescaya Wirasangka (Journal PEP Bandung, 2026)
Copper slag produced in industry can be 2 to 3 times as much as crude copper, and total waste emissions from copper slag have reached 50 million tons per year. In its treatment, industrial copper slag will only be stockpiled in one place, where, if it is dry, the high-metal-content copper slag will become fly dust and poison living creatures around it. Therefore, there is an urgency to resolve this problem. In recent years, researchers have continued to explore solutions to this problem. However, despite the large amount of research, the data scatter and become difficult for readers of the research report to digest. Therefore, to make things easier for academics, the author has created a study that summarizes the extent of research regarding solutions to the copper slag problem. This study will discuss how researchers have utilized copper slag waste. Some researchers use copper slag as a construction material, such as an admixture for concrete, a supplementary cementitious material for ordinary Portland cement, and a raw material to replace sand in road construction. Other researchers will approach chemical treatment as a solution. The author hopes, readers can dive in and join the journey towards full utilization of copper slag.